(untitled) (Heritage, 2021)
In this paper the author presents a part of the results of field research conducted among Serbs in Northern Kosovska Mitrovica between 2011 and 2014. The motive of the research was to offer a contribution to the understanding of the position of the Serbs in this city in the conditions of the altered socio-political context after the war on Kosovo and Metohija in 1999. A part of the research was paid to the problem of the image of Albanians in the perception of Serbs in the context of mutual conflict and the division of Kosovska Mitrovica into two parts – northern, majorly Serbian, and southern – majorly Albanian. This topic has imposed itself practically from the very beginning of the research, due to the fact that the Serbs in Kosovska Mitrovica generally defined their everyday life after the war in 1999 through the picture of division towards Albanians. Theoretically, the research was relied on the concept of ethnic identity, or ethnicity. Starting from Roland Barthes’ interpretation of this phenomenom, according to which it is reflective, what means defined by boundaries as a social product arising from the need of groups to differentiate between each other, the aim of the research was to provide ethnographic material useful for understanding the identity position of Serbs in Northern Kosovska Mitrovica in the conditions of conflict with Albanian ethnic group. Methodologically viewed, the research was conducted by using an anthropological approach, which meant that the studied problem was analyzed at the interpersonal level and through the experiences of individuals. Attention was focused on the discourse, which means that the research topic was observed from the point of view of the testimonies of the respondents included in the research. The testimonies of the respondents were obtained by using in-depth, ie qualitative research methods, in the first place formal and informal interviews. The research showed that the identity discourse of the Serbs in Northern Kosovska Mitrovica towards Albanians was marked by distance, imbued with feelings of threat and distrust. Members of the Albanian ethnic group were observed through the generalizing prism of opposing others, so that they were attributed characteristics with most often diametrically different sign compared to the characteristics that the respondents attributed to themselves, to their own, Serbian ethnic group. On the one hand, the respondents attributed negative characteristics to Albanians, which they considered as not appropriate for Serbs. These characteristics were observed at a double level: 1) regardless of contacts with Serbs (“uncultured”, “primitive”, “uncivilized”); and 2) in the context of mutual contacts (hypocritical, pretentious, cunning, calculated, etc), ie from the aspect of the attitude towards Serbs which was generally described as hostile. Negative characteristics attributed to Albanians respondents perceived as features opposite to the characteristics of Serbs, which means that by emphasizing them, according to the principal of mutual contrast, they implicitly pointed to the positive values of their own, Serbian identity. On the other hand, the respondents attributed certain positive characteristics to Albanians, namely those that they considered to be in favor of members of Albanian ethnic group in relation to Serbs, which the Serbs lacked. These characteristics were also treated in contrast to Serbian characteristics, and they meant patience, tact, wisdom, diligence, meekness, keeping a given word. The results presented in the paper upgrades the results of previous research that included the analyses of the image of Albanians in the perceptions of Serbs in Kosovo and Metohija in the conditions of the altered socio-political context in this area after the war in 1999. Presented ethnographic material, obtained in period between 2011 and 2014, showed that Serbs in Northern Kosovska Mitrovica perceived Albanians primarly through the prism of simplified ideas, which viewed from identity aspect implied the perception of members of the Albanian ethnic group as violent, and members of their own, Serbian ethnic group as victims. Generalization as a form of opinion about Albanians in the statements of respondents was coloured with the intertwining of negative and positive attitudes about the characteristics of members of the Albanian ethnic group, with the fact that these attitudes were expressed in such a way as to compare the characteristics of their own group. Yet, the research obtained several views which softened the contrast between Serbs and Albanians, by pointing out the elements of a social character common to each other. The image of Albanians, in the end, gained some complexity thanks to the attitudes of those respondents who spoke about members of this ethnic group through the perception of direct connections and personal experiences. This brought to light the attitude towards Albanian that in some measure deviated from the prevailing generalizations, which, from an analytical point of view, suggested that the image of members of this ethnic group in the perception of Serbs in Northern Kosovska Mitrovica was not as simplified as in the context of mutual conflict it might seem so at first glance.